Analisis pengaruh penambahan tepung okra dan tepung porang terhadap komposisi proksimat dan organoleptik foodbars - Erwin Nofiyanto; Aldila Sagitaning Putri (AGROINTEK, 2025)
Food not only provides a feeling of fullness, but is also beneficial for health and disease prevention. One type of food that has health benefits is functional food, one of which is food bars. Foodbars are made from a mixture of nutritionally enriched blended food such as grains, dried fruit and nuts which are then formed into a solid and compact food. One of the local food ingredients that is used as a substitute for making food bars is okra and porang. The aim of this research was to determine the effect of adding okra flour and porang flour on the proximate and organoleptic composition of Foodbars. The research method used an experimental design, namely a one-factor Completely Randomized Design (CRD), with treatment comparison between okra flour and porang flour (15:10, 12.5:12.5, 10:15). Each treatment was repeated 5 times. The variables observed were water content, ash, crude fiber, fat, protein, carbohydrates, and preference test. The data obtained were analyzed for variance and if there were differences between treatments, they were further tested using the Duncan Multiple Range Test (DMRT) at the 5% level. The research results of the addition of 12.5g okra flour and 12.5g porang flour are food bars with the best treatment in physicochemical testing and meet the requirements of commercial food bars according to SNI and are liked by consumers with a water content of 11.11%, ash 4.88%, crude fiber 27 .20, fat 26.38%, protein 12.42%, and carbohydrates 45.21%